Determination of polyurethane-grafted peptide (GSGREDVGSG) using bicinchoninic acid assay. (2018) - Butruk-Raszeja, Beata A; Kuźmińska, Aleksandra
The goal in the presented study was to develop a simple, fast and accurate method for measuring the surface density of a short peptide sequence bound to a polymeric substrate. We analyzed polyurethane samples chemically modified with acrylic acid and polyurethane-grafted peptide (GSGREDVGSG) and investigated the possibility of using the bicinchoninic acid (BCA) assay to determine surface density of the solid-supported peptide. We set the conditions (temperature, time) under which the test should be conducted. We also studied the interaction of the BCA reagent with polyurethane substrate and the effect of drying conditions as well as material type and form on the test response. We have proposed potential factors that might interfere with the BCA assay and chosen the proper control materials.